Ghadhul Bashar Menurut Syekh Ali Ash-Shabuni Dan Penerapannya Di Era Digital Dalam Kehidupan Generasi Z (Studi Kasus Desa Sanggalima Kec. Gebang Kab. Langkat) - Abdul Hamid; Kamalia R (Journal Smart Law, 2025)
This study examines the implementation of Ghadhdhul Bashar (lowering one's gaze) in the life of Generation Z in the digital era, focusing on the youth of Desa Sangga Lima Gebang Kab.Langkat. The study addresses the phenomenon of increasing free association and access to digital content that contradicts Islamic principles, such as unsupervised interactions between opposite genders. The research aims to explore Generation Z's behavioral patterns toward digital media and social interactions, as well as to evaluate the application of Ghadhdhul Bashar values as an educational solution. The study employs a qualitative approach using interviews, observations, and literature reviews as data collection techniques. The findings reveal that the implementation of Ghadhdhul Bashar is still minimal due to a lack of religious understanding, the influence of social media, and weak environmental control. This study recommends an educational approach based on Islamic values and increased collective awareness as a strategy to implement Islamic principles in the digital era. The research findings revealed that the main challenges in implementing ghadhul bashar in the digital age are influenced by technological and social factors. The Triple A Engine concept (accessibility, affordability, and anonymity) explains why immoral content is easily accessible and difficult for the younger generation to control.